Evaluation of land use and occupation considering the spatialization of precipitation in the northeastern Mato Grosso sub-basins - Cessa, Raphael Maia Aveiro; Medeiros Lustosa Junior, Ilvan; do Amaral, Uirá; Magno Moreira de Oliveira, Carlos Magno; Cometti, Nilton Nélio; Gimenes Rodrigues Silva, Felipe (Revista Agrogeoambiental, 2022)
This study aimed to analyze the use and land occupation considering the spatialization of precipitation in the hydrographic sub-basins (HS) in the northeast of the state of Mato Grosso. The data used to spatialize the mean accumulated rainfall in northeastern Mato Grosso considered the rainy season between October 1st and April 30th from 2016 to 2020. The isohyet map was obtained and stratified into three classes for discussion and data comparison. The delimitation of the HSs was carried out from a mosaic of images, generating a digital elevation model. To discuss the results, the mean accumulated rainfall isohyet map was superimposed on the HS map. Higher values of accumulated rainfall in the rainy season in northeastern Mato Grosso occur in its eastern portion in relatively lower altitudes, possibly related to the preference of the meteorological systems, which produces maximum (minimum) rainfall on the windward (leeward) of the mountains. In areas with a mean accumulated rainfall above 1,200, the occupations with forestry and grassland vegetation and managed pastures and agriculture add up to 49% and 23% of the total area, respectively. The study revealed that, in the northeast region of the state of Mato Grosso, the area occupied by the delimitation of the mean accumulated precipitation above 1,200 mm has 49% of its extension occupied with natural vegetation areas and 23% of its extension occupied with agricultural or livestock activities.